2017
DOI: 10.1016/j.celrep.2017.09.011
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Chromatin Switch in the Direct Reprogramming of Fibroblasts to Neurons

Abstract: SUMMARY How transcription factors (TFs) reprogram one cell lineage to another remains unclear. Here, we define chromatin accessibility changes induced by the proneural TF Ascl1 throughout conversion of fibroblasts into induced neuronal (iN) cells. Thousands of genomic loci are affected as early as 12 hours after Ascl1 induction. Surprisingly, over 80% of the accessibility changes occur between days 2 and 5 of the 3-week reprogramming process. This chromatin switch coincides with robust activation of endogenous… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

10
120
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 124 publications
(130 citation statements)
references
References 59 publications
10
120
0
Order By: Relevance
“…Chromatin modifiers, such as the EZH2 and ASCL1 components, are also useful for DR to iNSCs or motor neurons [183, 201203]. JMJD3 has been reported as an epigenetic enhancer of lineage conversion from bone marrow progenitors to liver cells [204].…”
Section: Potential Key Factors To Overcome the Obstacles To Cancer Cementioning
confidence: 99%
“…Chromatin modifiers, such as the EZH2 and ASCL1 components, are also useful for DR to iNSCs or motor neurons [183, 201203]. JMJD3 has been reported as an epigenetic enhancer of lineage conversion from bone marrow progenitors to liver cells [204].…”
Section: Potential Key Factors To Overcome the Obstacles To Cancer Cementioning
confidence: 99%
“…Pioneer TFs induce the expression of endogenous secondary pro-neuronal TFs or of factors that repress the starting cell type-specific transcriptome, which further contributes to establishing neuronal identity [27]. Chromatin accessibility and transcriptome data have suggested that Zfp238, Sox8, and Dlx3 are among the most important endogenous secondary TF genes downstream of Ascl1 [32]. Some data indicate that Ngn2, when using an appropriate conversion medium, not only binds most of the Ascl1 binding sites in fibroblasts, but also possesses many additional binding sites [30,33].…”
Section: Enabling In Conversionmentioning
confidence: 99%
“…One of the most commonly used TFs is the proneuronal gene achaete-scute homolog 1 (Ascl1). Many other TFs can also contribute to the reprogramming, such as brain-specific homeobox/POU domain protein 2 (Brn2) that does not access fibroblast chromatin actively on their own but it is recruited by Ascl1 [11,12]. Ascl1 alone can act as a pioneer factor occupying specific sites of the fibroblast genome [11].…”
mentioning
confidence: 99%
“…Ascl1 belongs to the family of the basic helix-loop-helix family, and it specifically binds DNA sequences containing an E-box motif [10]. Ascl1 alone can act as a pioneer factor occupying specific sites of the fibroblast genome [11]. Many other TFs can also contribute to the reprogramming, such as brain-specific homeobox/POU domain protein 2 (Brn2) that does not access fibroblast chromatin actively on their own but it is recruited by Ascl1 [11,12].…”
mentioning
confidence: 99%
See 1 more Smart Citation